Forming Student Characters With Learning Methods Concerning Human Rights in Indonesia - Adelia, Tasya (International Journal of Students Education, 2024)
Human Rights Education (HAM) is a strategic means to shape the character of students in Indonesia. The human rights-based learning method aims to develop students' awareness of fundamental values such as justice, humanity, and tolerance, as well as respect for basic rights. Through an interactive learning approach, including discussions, case studies, and simulations, students are invited to understand and internalize human rights principles directly in the context of everyday life. This approach is expected to foster empathy, integrity, and critical thinking skills that are the foundation for ethical character and care for the social environment. Thus, human rights education in Indonesia has the potential to form a young generation with integrity, broad insight, and is ready to contribute to realizing a more just and dignified society.